GPR45 Regulates Body Weight and Energy Homeostasis in Pro-opiomelanocortin Neurons - Yongyong Meng; Chengchen Hu; Tao Zhao; Simin Xie; Jing Cui; Lei Sun; Xiaohui Wu (Phenomics, 2026)

Porcine epidemic diarrhea virus influences the expression of tight junction proteins through the polarity protein PAR6 - Tingyu Hu; Ruolan Zhang; Qian Weng; Simin Wang; Yuheng Li; Zhihua Pei; Kai Wang; Guixue Hu (Virus Genes, 2026)

Carbon release from mangrove litter decay is regulated by polyethylene microplastics through the reshaping of the sediment microbiome - Simin Wang; Junjie Du; Weilu Kang; Shaohu Ouyang; Xiangang Hu; Qixing Zhou; Ruiren Zhou (Chemical Engineering Journal, 2026)

A hybrid inversion framework combining convolutional neural network surrogate modeling and data assimilation for efficient groundwater contamination characterization - Caiping Hu; Fuqiang Xu; Dexin Kong; Jia Li; Wenfeng Gao; JunZe Wei; Simin Jiang (Hydrogeology Journal, 2026)

A hybrid deep learning-data assimilation approach for joint inversion of groundwater contaminant sources and hydraulic conductivity with uncertain boundary conditions - Xuemin Xia; Yule Zhao; Simin Jiang; Yao Hu; Xianwen Li (Advances in Water Resources, 2026)

Assessment of the semipermeable membrane effect of illite and montmorillonite on dissolved thallium diffusion - Yu Liu; Simin Hu; Lezhang Wei; Dinggui Luo; Tangfu Xiao (Engineering Geology, 2026)

Convallatoxin ameliorates fibroblast-like synoviocytes-mediated synovial inflammation and joint destruction in rheumatoid arthritis by targeting IDH1 - Suling Liu; Huijuan Hu; Yu Kuang; Simin Chen; Kai Sun; Chenxi Peng; Ruiru Li; Fan Su; Liuqin Liang; Qian Qiu; Youjun Xiao; Hanshi Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

PEDV infection induces ferroptosis in Vero cells via an ACSL4-mediated lipid peroxidation pathway - Qian Weng; Yuheng Li; Yuze Wei; Simin Wang; Tingyu Hu; Zhihua Pei; Kai Wang; Guixue Hu (Archives of Virology, 2026)

Efficacy and safety of vunakizumab between super responders and non-super responders of patients with moderate-to-severe plaque psoriasis: a post-hoc exploratory analysis of a phase III trial - Ougen Liu; Caixia Kou; Simin Yu; Huizhong Hu; Xiaoxiao Chen; Meiying Jiang; Shifeng Ren (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Novel receptor-binding protein from phage PJNS004 for sensitive detection of Salmonella - Yibao Chen; Simin Yang; Qing Zhang; Ming Hu; Qianghua Lv; Xiaonan Zhao; Lulu Li; Yanbo Luo; Xiaohui Xu; Yujun Zhao; Yuqing Liu (Food Chemistry, 2025)

Temporin-GHaR Peptide Alleviates LPS-Induced Cognitive Impairment and Microglial Activation by Modulating Endoplasmic Reticulum Stress - Da-Qi Zhang; Xiaoqian Dong; Simin Su; Linlin Zhang; Jiayu Zhang; Wenjing Yang; Wenting Hu; Lushuang Li; Yanting Song; Xi Xie; Qifu Li; Rong Wang; et al. (Probiotics and Antimicrobial Proteins, 2025)

Simple synthesis and excellent performance of the cow dung–based biodegradable liquid mulch for sustainable agriculture - Xiaohao Guo; Yuankai Zhou; Simin Li; Zhiwen Li; Wei Liu; Yalan Zhang; Hu Du; Wenrong Xiong; Qi Li; Yanyan Zhong; Tian Qin; Mengting Wu; et al. (Environmental Research, 2025)

Cerebral [18F]AIF-FAPI-42-Based PET Imaging of Fibroblast Activation Protein for Non-invasive Quantification of Fibrosis After Ischemic Stroke - Peipei Tang; Yang Liu; Simin Peng; Zhikai Cai; Ganghua Tang; Zhou Zhou; Kongzhen Hu; Yuhua Zhong (Translational Stroke Research, 2025)

Remediation of thallium-contaminated groundwater using magnetic illite–biochar: Structural characteristics, performance and mechanisms - Simin Hu; Yu Liu; Lezhang Wei; Dinggui Luo; Qihang Wu; Xuexia Huang; Tangfu Xiao (Journal of Environmental Chemical Engineering, 2025)

Role of methanogenesis and methanotrophy in CH4 fluxes from rice paddies under elevated CO2 concentration and elevated temperature - Yuanyuan Wang; Zhenghua Hu; Botao Gu; Jingjing Xing; Chao Liu; Tingwu Liu; Simin Zhao; Xinyu Zhang; Luoyan Zhu; Ziqi Xu (Science of The Total Environment, 2024)

Global hydroclimate perturbations during the Toarcian oceanic anoxic event - David B. Kemp; Zhong Han; Xiumian Hu; Wenhan Chen; Simin Jin; Kentaro Izumi; Qing Yan; Viktória Baranyi; Xin Jin; Jacopo Dal Corso; Yuzhu Ge (Earth-Science Reviews, 2024)

Porcine kobuvirus enhances porcine epidemic diarrhea virus pathogenicity and alters the number of intestinal lymphocytes in piglets - Simin Wu; Fang Gou; Jie Meng; Xin Jin; Wanchen Liu; Weishuai Ding; Weihang Xu; Changqin Gu; Xueying Hu; Guofu Cheng; Pan Tao; Wanpo Zhang (Veterinary Microbiology, 2024)

Efficient zero wastewater and salt-free of cotton fiber dyeing via hydrophobic organic chemical/water two-phase dyeing system - He Zhu; Liujun Pei; Jingyuan Yi; Simin Sun; Qiushuang Hu; Jiping Wang; Zongqian Wang (Journal of Cleaner Production, 2024)

Recent advances in clay minerals for groundwater pollution control and remediation - Simin Hu; Yu Liu; Lezhang Wei; Dinggui Luo; Qihang Wu; Xuexia Huang; Tangfu Xiao (Environmental Science and Pollution Research, 2024)

Polyethylene microplastic-induced microbial shifts affected greenhouse gas emissions during litter decomposition in coastal wetland sediments - Simin Wang; Qixing Zhou; Xiangang Hu; Zongxin Tao (Water Research, 2024)

Hydrogeochemical evolution of groundwater impacted by acid mine drainage (AMD) from polymetallic mining areas (South China) - Yu Liu; Xianming Xie; Song Wang; Simin Hu; Lezhang Wei; Qihang Wu; Dinggui Luo; Tangfu Xiao (Journal of Contaminant Hydrology, 2023)

Tropical ocean temperatures and changes in terrigenous flux during the Paleocene-Eocene Thermal Maximum in southern Tibet - Simin Jin; Guobiao Li; Juan Li; Xiumian Hu; Huan Yang; Chunju Huang; Zhantu Baoke; Thomas J. Algeo; David B. Kemp (Global and Planetary Change, 2023)

A multiple-methods approach to investigate dietary differences among nominally herbivorous fishes - Xianzhi Lin; Simin Hu; Yanyan Zhou; Hui Huang; Li Zhang; Sheng Liu (Marine Biology, 2023)

Molecular quantification of copepod Acartia erythraea feeding on different algae preys - Simin Hu; Tao Li; Hui Huang; Sheng Liu (Acta Oceanologica Sinica, 2023)

Hydrogeochemistry of groundwater surrounding a pyrite mine in southern China: Assessment of the diffusive gradients in thin films technique for in situ monitoring - Yu Liu; Lezhang Wei; Hongmei Deng; Simin Hu; Xianming Xie; Dinggui Luo; Tangfu Xiao (Journal of Hydrology, 2023)

Unsynchronized migrations of different salt ions and ice microstructure development during unidirectional freeze-thaw - Ruiqi Wang; Yaxian Hu; Xinhao Yuan; Junying Chen; Simin Jiang; Xianwen Li (Desalination, 2023)

Utilization of ovalbumin-propylene glycol alginate complex system for superior foam: The effect of pH-driven phase behavior - Xinyue Zhang; Zizhen Sun; Qi Zeng; Haobo Jin; Simin Wang; Yongguo Jin; Yu Hu; Zhaoxia Cai (Food Hydrocolloids, 2023)

Progressively thawed soil layers differed in microbial properties and CO2 emission rates - Yaxian Hu; Xianwen Li; Huimin Liu; Xinhao Yuan; Simin Jiang; Xiaorong Wei (CATENA, 2023)

Short-term responses of phytoplankton size-fractionated structure and photosynthetic physiology to thermal effluent in a subtropical coastal bay - Simin Hu; Chen Zhang; Qingxia Liu; Tao Li; Hui Huang; Sheng Liu (Frontiers in Marine Science, 2023)
Elevated water temperature caused by the thermal discharge from power plants can exert multiple ecological impacts on the phytoplankton community in coastal ecosystems. Most recent studies have focused on the reshaping effects on the community structure; however, the short-term response of phytoplankton physiology to thermal discharge remains unclear. This study conducted research on the scope of thermal discharge from the nuclear power plant and the size-fractionated phytoplankton structure combined with photosynthetic physiology in Daya Bay, China. The thermal discharge significantly affected the surface temperature in the outlet regions, and the thermal plume mainly diffused along the northeast coast of the outfall site, resulting in a significant difference in the surface temperature between the inlet and outlet transects ( p< 0.05). Elevated surface temperatures decreased the total chlorophyll a concentrations by 33.19% at the outlet regions, with pico-phytoplankton decreasing the most. Chlorophyll a concentrations were higher at sites further away from the outlets, indicating that elevated water temperature might stimulate the rapid growth of phytoplankton, especially nano-phytoplankton which replaced pico-phytoplankton as the dominant group at stations away from the outlets. Significant negative correlations were observed between the photochemical quantum yield ( F v /F m ) and temperature ( p< 0.05), and the relative electron transport rate (rETR) and temperature ( p< 0.05). Phytoplankton showed a normal photosynthetic physiological state at most sites with a surface temperature<33°C but was severely affected at the outlet site with a 5°C rise, decreasing from ~0.5 on the inlet transect to 0.07. During the diurnal survey, the high temperatures near the outlet at midday had a compensatory effect on phytoplankton’s light suppression. The results indicated that the physiological state of phytoplankton was clearly influenced by the thermal discharge with diurnal variation, and different size-fractionated phytoplankton groups exhibited heterogeneous responses. The findings may provide further insights into the ecological impacts of thermal discharges as well as global warming in subtropical regions.

Low-Cd wheat varieties and soil Cd safety thresholds for local soil health management in south Jiangsu province, east China - Pengjie Hu; Feng Tu; Simin Li; Yunjun Pan; Cheng Kong; Xumei Zhang; Shaohua Wang; Yongquan Sun; Dan Qiu; Longhua Wu; Yongming Luo; Peter Christie (Agriculture, Ecosystems & Environment, 2023)

Microbial communities associated with epilithic algal matrix with different morphological characters in Luhuitou fringing reef - Tiancheng Zhou; Simin Hu; Nan Jia; Chen Zhang; Hui Huang; Sheng Liu (Frontiers in Marine Science, 2022)
The microbiota is an important component of the epilithic algal matrix (EAM) and plays a central role in the biogeochemical cycling of important nutrients in coral reef ecosystems. Insufficient studies on EAM microbiota diversity have led to a limited understanding of the ecological functions of EAMs in different states. To explore the microbial community of EAMs in the Luhuitou fringing reef in Sanya, China, which has undergone the incessant expansion and domination of algae over the past several decades, investigations were conducted in the reef’s intertidal zone. Five types of substrate habitats (dead branching coral, dead massive coral, dead flat coral, granite block, and concrete block) were selected, and their microbial communities were analyzed by high-throughput sequencing of EAM holobionts using the 16S rDNA V4 region. Proteobacteria was the most abundant group, accounting for more than 70% of reads of the microbial composition across all sites, followed by Cyanobacteria (15.89%) and Bacteroidetes (5.93%), respectively. Cluster analysis divided all microbial communities into three groups, namely short, medium, and long EAMs. Algal length was the most important morphological factor impacting the differences in the composition of the EAM microbiota. The three EAM groups had 52 common OTUs and 78.52% common sequences, among which the most abundant were Vibrio spp. and Photobacterium spp. The three types of EAM also had unique OTUs. The short EAMs had 238 unique OTUs and 48.61% unique sequences, mainly in the genera Shewanella and Cyanobacterium . The medium EAMs contained 130 unique OTUs and 4.36% unique sequences, mainly in the genera Pseudomonas and Bacillus . The long EAMs only had 27 unique OTUs and 4.13% unique sequences, mainly in the genus Marinobacter . Compared with short EAM, medium and long EAM had a lower proportion of autotrophic bacteria and higher proportion of potential pathogenic bacteria. It is suggested that EAMs with different phenotypes have different microbial compositions, and the ecological function of the EAM microbiota changes from autotrophic to pathogenic with an increase in algal length. As EAMs have expanded on coastal coral reefs worldwide, it is essential to comprehensively explore the community structure and ecological role of their microbial communities.

Disturbance-Mediated Changes in Coral Reef Habitat Provoke a Positive Feeding Response in a Major Coral Reef Detritivore, Ctenochaetus striatus - Xianzhi Lin; Simin Hu; Yong Liu; Li Zhang; Hui Huang; Sheng Liu (Frontiers in Marine Science, 2021)
Coral reefs are undergoing global phase shifts from coral-dominated to algae-dominated stages. The negative effects of this substratum shift on the diversity and abundance of fish have been well documented, but the influence on fish feeding is less studied, which may limit a deeper understanding of trophic pathways in such a disturbed system. In this study, we investigated the feeding response of a numerically dominant fish species Ctenochaetus striatus to different substrate types, including hard coral, short algal turfs (SATs, <5 mm), and long algal turfs (LATs, >5 mm), on reefs in the South China Sea. The biomass of C. striatus showed an inverted U-shaped relationship with coral coverage and a significant positive correlation with SAT coverage ( p < 0.05), indicating that rising SAT coverage associated with moderate coral loss provoked a feeding response in C. striatus . Stomach contents of C. striatus , analyzed using high-throughput sequencing (HTS), were dominated by algal sequences (relative read abundance, RRA > 80.0%), including macroalgae, filamentous algae, and microalgae (e.g., Symbiodinium and Prorocentrum ). The sequence number and diversity of microalgae (mainly dinoflagellates) tended to be abundant (RRA 13.5–36.5%) with increased SAT cover, but brown algae sequences (RRA 17.2–57.8%) or green algae sequences (RRA > 50.7% except one site) dominated the stomach content DNA in reefs with high coral cover and high LAT or macroalgal cover, respectively. Considering the limited ability of C. striatus to remove mature algae, macroalgal DNA might be from algal debris. Our results indicate that C. striatus populations respond positively to conditions of moderate coral loss through increases in body condition identified as increased biomass. These responses are correlated to the expansion of SAT’s as coral cover declined, however, this relationship reverses if coral loss is high due to the succession of LAT’s over SAT’s and a corresponding decrease in the quality of food available. Our use of HTS has nevertheless identified the importance of detritivory in the flow of energy through reefs in the Anthropocene which are increasingly becoming depauperate in hard coral.

Mechanisms of high-frequency dinoflagellate blooms of Scrippsiella trochoidea in Daya Bay, South China Sea - Yuan Tian; Simin Hu; Xianzhi Lin; Hui Huang; Xingyu Song; Yan Yan; Xuedong Xie; Tao Li; Sheng Liu (Journal of Oceanology and Limnology, 2021)

Small Jellyfish as a Supplementary Autumnal Food Source for Juvenile Chaetognaths in Sanya Bay, China - Lingli Wang; Minglan Guo; Tao Li; Hui Huang; Sheng Liu; Simin Hu (Journal of Marine Science and Engineering, 2020)
Information on the in situ diet of juvenile chaetognaths is critical for understanding the population recruitment of chaetognaths and their functional roles in marine food web. In this study, a molecular method based on PCR amplification targeted on 18S rDNA was applied to investigate the diet composition of juvenile Flaccisagitta enflata collected in summer and autumn in Sanya Bay, China. Diverse diet species were detected in the gut contents of juvenile F. enflata, including copepods, small jellyfish, anthozoa, polychaetes, echinoderms, diatoms and dinoflagellates. The diet composition showed obvious differences between summer and autumn. Copepod, such as Temora turbinata, Canthocalanus pauper and Subeucalanus crassus, dominated the diet in summer, representing up to 61% of the total prey items. However, small jellyfish, mainly consisting of Bougainvillia fulva, Solmissus marshalli and Pleurobrachia globosa, was the main food group (72.9%) in autumn. Environmental parameters showed no significant difference between summer and autumn. The mean abundance of juvenile chaetognaths in autumn was about eight times higher than that in summer, while the abundance of potential food prey was similar in both seasons. Our results suggested that juveniles chaetognaths might consume small jellyfish as a supplementary food source under enhanced feeding competition in autumn.

Dietary separation between co-occurring copepods in a food-limited tropical coral reef of the Sanya Bay - Simin Hu; Tao Li; Sheng Liu; Hui Huang (Acta Oceanologica Sinica, 2020)

Flexible feeding patterns of copepod Centropages tenuiremis in fluctuating conditions: a possible survival strategy to cope with disturbance - Cuilian Xu; Simin Hu; Zhiling Guo; Tao Li; Hui Huang; Leo Lai Chan; Sheng Liu (Acta Oceanologica Sinica, 2020)

Sub-chronic exposure to Tris(1,3-dichloro-2-propyl) phosphate induces sex-dependent hepatotoxicity in rats - Simin Wang; Xiangang Hu; Xueyan Li (Environmental Science and Pollution Research, 2019)